Thermogravimetric catalytic pyrolysis and kinetic studies of coconut copra and rice husk for possible maximum production of pyrolysis oil - Vekes, Balasundram; Norazana, Ibrahim; Rafiziana, Md Kasmani; Mohd. Kamaruddin, Abd. Hamid; Ruzinah, Isha; Hasrinah, Hasbullah; Roshafima, Rasit Ali (Elsevier, 2017)
The main objective of the present work is to study the effect of Nickel-Cerium/Alumina multifunctional catalyst (Ni-Ce/Al2O3) mass loading on pyrolysis of coconut copra and rice husk via thermogravimetric analysis. The sample is pyrolyzed from 30 C up to 700 C at a constant heating rate of 10 C/min in nitrogen environment flowing at 150 mL/min. The multifunctional catalyst (Ni-Ce/Al2O3) was prepared via incipient wet impregnation method. Pyrolysis feedstocks were prepared based on biomass to catalyst mass loading ratio. The TG-DTG curve shows that the presences of catalyst significantly affect the devolatilization rate of biomass. Among TGA-pyrolyzed coconut copra samples, the CC-3 (1:0.15) has achieved the highest mass loss (83.3%). For rice husk, the non-catalytic sample has attained the highest mass loss of volatile matter (48.7%). In addition, the kinetic characteristics of non-catalytic and catalytic pyrolysis of biomass were also studied and calculated by employing the Coats-Redfern integral method. The CC-1 has lower activation energy (53.10 kJ/mol) than that of catalytic sample particularly CC-3 (79.28 kJ/mol). The presence of a catalyst on rice husk is able to reduce the activation energy of noncatalytic rice husk sample from 49.78 to 45.24 kJ/mol.